Motherhood in Nepal during COVID-19 Pandemic: Are We Heading from Safe to Unsafe? - Aryal, Shreyashi; Shrestha, Deepak (Journal of Lumbini Medical College, 2020)
Safe Motherhood Program (SMP) has been one of the successful ongoing maternal health programs in Nepal. It is the major reason for Nepal being able to reduce its Maternal Mortality Ratio (MMR) significantly falling from 539 to 281 deaths per 100000 live births over the decades. SMP has nine components out of which three components mainly deal with pregnancy and puerperium; birth preparedness plan, rural ultrasound program and the “Aama and New born Program”. The latter one is one of the key components of SMP which includes incentives, free delivery services and free sick newborn care. Financial incentives are provided for transport and completion of four antenatal visits, and for health care workers attending deliveries. However, with the corona virus disease (COVID-19) pandemic, this program might not be enough to ascertain a safe motherhood for Nepalese women. This program aims to reduce the three delays leading to maternal morbidity and mortality namely, delay in reaching care, seeking care and receiving care. But with a nationwide lockdown, the chances of these delays have increased even more.